Avaliação do conhecimento sobre algumas zoonoses com proprietários de cães da área urbana do município de Botucatu, SP - Tomé, Rozeani Olímpio [UNESP] (2010)
The search intended to evaluate the zoonosis perceptions of the dogs’ owners from urban areas in Botucatu-SP. A questionnaire with questions on rabies, leishmaniosis, leptospirosis and toxoplasmosis was applied to 333 dogs’ owners. The descriptive statistic analysis showed that 325 of these owners have already heard about rabies, 133 associated this disease to “mad dog disease” and 272 defended the dogs’ and cats’ annual vaccination as a means of preventing rabies. The leishmaniosis was known by 269 subjects, but 230 ignored how it was transmitted to human beings. Concerning leptospirosis, 251 people knew the disease, 139 did not know how the humans were affected. About toxoplasmosis, 282 subjects ignore what the disease is, 268 ignore the intake of meat as a means of toxoplasmosis transmission. From these results, one can confirm the need of the advertisement action development that magnify the community knowledge about these zoonosis.